Resolution of Compensation for Crime Victims as the Responsibility of the State through the LPSK Institution Examined from the Perspective of Legal Certainty - Rosalina Indah Sari (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The state, through LPSK (the Witness and Victim Protection Agency), serves as the forefront in resolving compensation issues for crime victims, as a form of responsibility and guarantee from the state to its citizens, as well as protection for crime victims. LPSK, an abbreviation for the Witness and Victim Protection Agency, is an institution tasked with providing protection and rights to witnesses and/or victims, in accordance with Law Number 13 of 2006 concerning Witness and Victim Protection. The guarantee provided by the state through LPSK is the right to equal legal certainty. This has been emphasized in Article 28D, paragraph (1) of the 1945 Constitution, which states that